Breast Modeling Towards an Educational Tool for Breast Cancer Surgeons - Daniela do Vale Afonso (2019)
Breast deformities that occur due to possible complications or procedures of breast cancer removal surgery can have an impact on its physical appearance and adversely affect the psychological state of the person concerned. This psychological impacts happens particularly in women, since the breast is socially seen as an icon of femininity and fertility. When diagnosed with breast cancer, the most frequent treatments are radiation therapy, chemotherapy, and surgery. Within the surgeries, mastectomy is the one that most women fear since the intervention is more radical and quite invasive due to the fact that all the breast tissues are removed. Nonetheless, there are less radical alternatives such as the conservative treatment of breast cancer, which is less invasive and preserves more the breast aesthetics because it only removes the tumor and some surrounding tissues. The latest techniques such as Breast Conserving Surgery (BCS) aims to achieve greater efficiency and a better aesthetic result. Although there are very heterogeneous practices that lead to different aesthetic results. Creating an educational training framework for conservative surgery may be very useful for newly trained surgeons. The framework will help them become better professionals before obtaining experience, since there is a relationship between experience and the outcome of a surgery. Studies show that the result of a surgery can be influenced by the experience of the surgeons, ie, the more experience (number of surgeries performed) the surgeon has, better are the results obtained. In order to create a training framework, parametric and synthetic 3D models were used to simulate the surface of the breast (with or without deformities), its interior and other structures such as thorax and pectoral muscle. The inputs required to simulate the breast surface are volume, breast type and its projection. The breast density is represented by 4 types of Breast Imaging-Reporting and Data System (BI-RADS) classification. To represent the tumor in the model it is essential to know the quadrant in the breast, its stage of development and the tumor form, round or speculated. The educational tool has an interface, previously tested and validated for its usability and effectiveness between several interface prototypes.